2011
DOI: 10.1063/1.3559489
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of effective ion pair interactions in warm dense beryllium and helium plasmas within integral equation theory

Abstract: Under hypernetted chain ͑HNC͒ approximation, effective ion pair interaction potentials for the warm dense matter are extracted by using available radial distribution functions ͑RDFs͒. The effective ion pair potentials extracted from first-principles simulation results are found containing the short-ranged attraction ͑SRA͒ component for both warm dense helium and beryllium plasmas. The SRA potentials can be well represented by Gaussian functions in both cases and then the extracted effective ion potentials are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…At temperatures below 4 eV, the PCF computed with the SC-MD method are dramatically different from those computed with DFT-MD or EFF-MD. In particular, the short-range behavior of the PCF from our SC-MD simulations is indicative of a potential that is too soft at small r. This is consistent with previous studies where a short-range repulsive modification to an LSC potential was shown to improve agreement with DFT-MD [36,37]. This approach is based on finding a potential that gives a solution to the Ornstein-Zernicke integral equations www.cpp-journal.org that is consistent with data from DFT-MD.…”
Section: Pair Correlation Functionssupporting
confidence: 91%
See 2 more Smart Citations
“…At temperatures below 4 eV, the PCF computed with the SC-MD method are dramatically different from those computed with DFT-MD or EFF-MD. In particular, the short-range behavior of the PCF from our SC-MD simulations is indicative of a potential that is too soft at small r. This is consistent with previous studies where a short-range repulsive modification to an LSC potential was shown to improve agreement with DFT-MD [36,37]. This approach is based on finding a potential that gives a solution to the Ornstein-Zernicke integral equations www.cpp-journal.org that is consistent with data from DFT-MD.…”
Section: Pair Correlation Functionssupporting
confidence: 91%
“…For all temperatures where we have reported the ionic specific heat, we set Z = 3.2e and κ = 2.6Å −1 . The shape of the LSC potential at short range is not consistent with the DFT-MD force-matched potentials, so we expect that it will not provide a good description of carbon at the conditions studied here, in agreement with what has been observed in previous studies of other elements where a correction to the LSC has been applied at short range [36,37,40].…”
Section: Specific Heatsupporting
confidence: 68%
See 1 more Smart Citation
“…For a few years, the behavior of warm dense beryllium has been an issue of interest from both a theoretical and experimental point of view [15,16,17,18,19,20,13]. The recent possibility to carry out comparisons with different approaches motivates our interest to develop a pure classical investigation based on classical MD.…”
Section: Application To Berylliummentioning
confidence: 99%
“…The complexity of WDM, compressions and temperatures involved call for simplifications without sacrificing accuracy. Thus molecular dynamics (MD), i.e., classical simulations, using various effective potentials have been a focus of some recent studies [8,9]. Such methods were used in earlier work [10], often with phenomenological or 'chemical' models for pairinteractions, and in recent studies as well [12].…”
Section: Introductionmentioning
confidence: 99%